Architecture design of BeiDou global navigation signals - Shuren Guo; Chengeng Su; Feiren Lv (Geo-spatial Information Science)
Navigation signals play a crucial role in determining the performance and user experience of Global Navigation Satellite System (GNSS). In recent years, GNSSs have been actively modernizing their signal architectures to meet the increasing demand for high precision, robustness, specialization, and internationalization services. However, signals of the second-generation BeiDou Navigation Satellite System (BDS-2) have been struggling to keep pace with these rapid advancements. Thus, it is necessary to design modern signals to satisfy various demands of the existing and new users. To this end, this paper systematically outlines the requirements and challenges associated with the third-generation BeiDou Navigation Satellite System (BDS-3) signals from the design perspective. In addition, the comprehensive evaluation criteria and design achievements of BDS-3 signals are introduced. Further, the signal evolution during the transition from BDS-2 to BDS-3, along with strategies for user adoption, is presented. Moreover, global observation data are utilized to validate the performance of BDS-3 and other GNSS signals. The research findings presented in this study unequivocally affirm the successful realization of signal design objectives. Firstly, BDS-3 signals exhibit compatibility with BDS-2 signals, ensuring the continuity of services for existing users while facilitating a seamless transition and technological advancements. In addition, the performance of BDS-3 signals is on par with that of other modern GNSS signals, reaching the world-class level. Finally, BDS-3 signals are compatible and interoperable with various GNSS signals while supporting diverse and specialized services. The results presented in this study contribute to a comprehensive understanding of the signal architecture and evolution strategies of BDS-3 signals, offering valuable insights for the design and development of user terminals, which can maximize the multifaceted advantages of BDS.